2017
DOI: 10.1186/s12711-017-0287-4
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study in a large F2-cross of laying hens reveals novel genomic regions associated with feather pecking and aggressive pecking behavior

Abstract: BackgroundFeather pecking and aggressive pecking in laying hens are serious economic and welfare issues. In spite of extensive research on feather pecking during the last decades, the motivation for this behavior is still not clear. A small to moderate heritability has frequently been reported for these traits. Recently, we identified several single-nucleotide polymorphisms (SNPs) associated with feather pecking by mapping selection signatures in two divergent feather pecking lines. Here, we performed a genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Brinker et al [41] found a GABAergic system related candidate gene (GABBR2, Chromosome 2) for direct genetic effects for survival time which is linked to cannibalism in crossbred laying hens. Lutz et al [6] found a candidate gene (SLC12A9) on Chromosome 9 for FPD in a study of a large F2 cross of the HFP and LFP lines. The SCL12 gene family plays a role in the GABAergic system as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brinker et al [41] found a GABAergic system related candidate gene (GABBR2, Chromosome 2) for direct genetic effects for survival time which is linked to cannibalism in crossbred laying hens. Lutz et al [6] found a candidate gene (SLC12A9) on Chromosome 9 for FPD in a study of a large F2 cross of the HFP and LFP lines. The SCL12 gene family plays a role in the GABAergic system as well.…”
Section: Discussionmentioning
confidence: 99%
“…Low to medium heritabilities were frequently found [2,3] indicating the possibility to breed for this trait which has also been proven in several selection experiments [4]. A number of mapping studies revealed quantitative trait loci (QTL) and trait-associated genome-regions, but also highlighted the quantitative and complex nature of this trait [5,6], because the few significant QTL by far did not explain the total genetic variance. One approach to identify candidate regions in the genome is to map selection signatures in selected lines.…”
Section: Introductionmentioning
confidence: 99%
“…Another way of modeling population structure is to fit principal components (Patterson et al, 2006), but, as Hayes (2013) pointed out, it is not exactly traceable which variation source they actually remove. It may be noted that removing population structure effects is not straightforward when generalized linear models (e.g., Poisson models) are applied (Lutz et al, 2017).…”
Section: Single-marker Modelsmentioning
confidence: 99%
“…On the basis of the typical brain monoamine levels, we propose that aggressiveness may be related to the ADR genes based on the observed relative differences in brain NE level. Aggressiveness is determined by several genes and neurotransmitters [70][71][72][73][74][75][76] . Identification of these factors may help elucidate their modes of action.…”
Section: Discussionmentioning
confidence: 99%